Growth and survival of fingerlings of a threatened snakehead, Channa striatus (Bloch) in earthen nursery ponds - Rahman, Md. Aminur; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Shamsudin, Mariana Nor (Academic Journals, 2013)
Nursery rearing of a high-valued threatened snakehead fish, Channa striatus was studied in relation to varying stocking densities in earthen ponds. The experiment was conducted for eight weeks in nine earthen nursery ponds having an area of 0.012 ha with an average depth of 0.8 m. Fry produced from natural propagation was first reared in indoor cemented cisterns with hatched Artemia cyst as live food for 10 days and then stocked at 150,000, 200,000 and 250,000 ha-1 in treatment-1 (T1), treatment-2 (T2) and treatment-3 (T3), respectively. At stocking, mean length and weight of fry was 1.17±0.18 cm and 0.15±0.03 g, respectively. Fry in all the experimental ponds were fed with a supplementary feed comprising of fish meal (50%) and mustard oil cake (50%) at the rate of 5-8% of the estimated body weight. In addition, chopped trash fishes were supplied at the rate of 5% of the estimated biomass daily, till harvest. The physicochemical parameters of water and plankton were monitored simultaneously and were within the acceptable range for fish culture. Growth parameters (final weight, final length, weight gain, length gain and specific growth rate) and survival of fingerlings were significantly higher in T1 than those in T2 and T3, respectively. Feed Conversion Ratio (FCR) was significantly lower in T1 followed by T2 and T3 in that order. Significantly higher survival of fingerlings was obtained in T1 than those in T2 and T3. Overall, highest growth and survival were obtained from T1 where stocking density of fry was 150,000 ha-1. Hence, of the treatments evaluated, stocking density of 150,000 fry ha-1 appears to be the most efficient stocking density for rearing of C. striatus fingerlings in earthen nursery ponds. This study represents the first successful attempt to produce fingerlings of the threatened C. striatus in nursery ponds, the findings of which might immensely be helpful towards the protection of snakehead from extinction as well as for its conservation, stock enhancement and rehabilitation.